Halal tourism in non-Muslim destinations: A systematic literature review of meaning contestation, misconceptions, and collaborative governance - Ebtana Sella Mayang Fitri; Septi Sedyaning Hanurani; Ridho Gata Wijaya; Andris Adhitra; Mazin Abed Mohammed (Jurnal Pendidikan Vokasi, 2026)
This study provides a systematic literature review of halal tourism in non-Muslim and multicultural destinations, focusing on rejection, misconceptions, and meaning contestation in Indonesia. Following an adapted SALSA framework and PRISMA-informed screening process, relevant studies published between 2016 and 2025 were systematically identified from major international and Indonesian academic databases. After staged screening, 23 eligible publications were synthesized through two-round thematic content analysis. Guided by symbolic threat theory, framing theory, and collaborative governance, the review identified four recurring themes: halal food and certification, destination branding and identity, regulation, and social rejection. The findings indicate that public resistance is primarily driven by misconceptions that equate halal tourism with Islamisation and threats to local cultural identity rather than opposition to Muslim-friendly services themselves. Comparative evidence from Japan, South Korea, Thailand, and Morocco further demonstrates that inclusive Muslim-friendly service approaches are more socially acceptable than normative halal destination branding. This review contributes an integrated explanatory framework linking policy framing, symbolic threat, misconceptions, and collaborative governance to explain resistance toward halal tourism in multicultural destinations. The findings provide practical guidance for promoting inclusive Muslim-friendly services, strengthening evidence-based public communication, and developing collaborative governance strategies to enhance socially sustainable tourism development.